Educational and Instructional Technology in EFL/ESL Classrooms: A Literature Review - Al-Maashani, Salim; Mudhsh, Badri Abdulhakim (International Journal of Language and Literary Studies, 2023)
Technology in education has a significant impact on how new and creative types of assistance are offered to instructors, students, and the learning process as a whole. This review paper presents a literature review on educational and instructional technology in EFL/ESL classrooms. Utilizing the qualitative method, which relies solely on the collection of materials and findings from previous studies, such as books, papers, and articles, was employed. In addition, this review paper seeks to make the perspectives of earlier academics more visible and distinct. The study sheds light on whether technology enhances and influences the vocabulary, grammar, speaking, and reading skills of students. Based on the existing literature, technology in education is promising and a vital tool, especially in language learning. The findings have shown that there is a strong positive correlation between technology and language learning. Also, technology is the best helper, facilitator, and motivational factor in the classroom environment. Teachers are encouraged to use technology in teaching language skills, especially CALL, and wait to see positive results from their students. Finally, it is also advised that teachers educate themselves to become proficient in using different technology tools with their students. Ultimately, doing so, will lead them to enjoy teaching challenging subjects to their students using technology.